EXHAUST ANALYSIS AND PERFORMANCE OF A SINGLE CYLINDER DIESEL ENGINE RUN ON DUAL FUELS MODE - Miqdam Tariq Chaichan (Journal of Engineering, 2011)
Generally fossil based fuels are used in internal combustion engines as an energy source. Excessive use of fossil based fuels diminishes present reserves and increases the air pollution in urban areas. This enhances the importance of the effective use of present reserves and/or to develop new alternative fuels, which are environment friendly. Use of alternative fuel is a way of emission control. The term “Alternative Gaseous Fuels” relates to a wide range of fuels that are in the gaseous state at ambient conditions, whether when used on their own or as components of mixtures with other fuels. In this study, a single cylinder diesel engine was modified to use LPG in dual fuel mode to study the performance, emission, and combustion characteristics. The primary fuel, liquefied petroleum gas (LPG), was mixed with air, compressed, and ignited by a small pilot spray of diesel. Dual fuel engine showed a reduction in oxides of nitrogen in the entire load range. The brake thermal efficiency improved by 3% in dual fuel mode, especially at low load, and also reduced the hydrocarbon, carbon monoxide, and CO2 emissions.